Hubungan Antara Body Image Dengan Psychological Well Being Mahasiswa Universitas Nurul Hasanah Kutacane - Siska Putri Belangi (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by the mental health phenomena experienced by students. The aim of this research is to determine the relationship between body image and psychological well-being of Nurul Hasanah Kutacane University students. This research is quantitative research using relevant quantitative methods. The population in this study was 62 students in Public Health Sciences class A, B and C. This research sample consisted of 62 students using saturated sampling techniques. In data collection. The researcher used a psychological scale for data collection techniques. The type of data collection used a Likert scale in the form of a body image scale (ɑ = 0.797) and a psychological well-being scale (ɑ = 0.948). The data analysis technique uses Pearson product moment correlation with the help of SPSS 22.0. The results of this research data analysis show that there is a correlation coefficient (rxy) of 0.246 and a significance of 0.027 <0.05, which means there is a significant positive correlation between student body image and psychological well-being at Nurul Hasanah Kutacane University. The impact of body image on mental health. In this case, the learning speed is 6.1%.